Prevalence of Salmonella spp. in fresh fish and shrimp in Semarang’s Traditional Markets (Indonesia) through Polymerase Chain Reaction - ULFAH AMALIA; Y. S. DARMANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Amalia U, Darmanto YS. 2020. Prevalence of Salmonella spp. in fresh fish and shrimp in Semarang’s Traditional Markets (Indonesia) through Polymerase Chain Reaction. Biodiversitas 21: 2500-2505. Fresh fish products are rich in macronutrients for meeting the protein needs of the consumer's community. Semarang is a city located in the North Coast of Java, indirectly closely related to the production of catches and processed fish and shrimp, including several large markets in Semarang, e.g.: Rejomulyo, Jatingaleh, and Rasamala. The problem was that there are still many fresh fish and shrimp traders in traditional markets who did not understand how to handling of fresh fish and shrimp properly so that it triggers the growth of bacteria, one of which is Salmonella spp. Indonesian National Standard requires that Salmonella must be negative in food, because these bacteria are pathogenic. Generally, detection of Salmonella in food using conventional methods requires 5 days. This study aims to determine how far the prevalence of Salmonella in fresh fish and shrimps in three traditional markets in Semarang through Polymerase Chain Reaction, Real-Time PCR compare with conventional methods. The results showed that 4 out of 9 fresh fish samples (44%) and also 5 out of 9 fresh shrimp samples (55.6%) in three traditional markets in Semarang was contaminated by Salmonella spp through conventional method; while all of samples (100%) was detected Salmonella spp using PCR.